Honeycomb structure and manufacturing method thereof

JP2024143855A5Active Publication Date: 2025-01-31NGK CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023056768
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2025-01-31
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

Honeycomb structures with high cordierite content face challenges in achieving both high particulate collection efficiency and low pressure drop performance, necessitating improvements in thermal shock resistance and pore size distribution.

Method used

A honeycomb structure with a specific composition and manufacturing method, incorporating cordierite, ceria, and additional compounds like mullite, spinel, and cristobalite, with controlled pore size distribution and porosity, achieved by precise firing conditions, to enhance thermal shock resistance and performance.

Benefits of technology

The structure achieves both high particulate collection efficiency and low pressure drop performance, leveraging crystalline cordierite's thermal shock resistance while optimizing pore size distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a honeycomb structure capable of achieving both high collection efficiency and low pressure loss performance for particulates in a higher dimension while utilizing excellent thermal shock resistance which is a characteristic of crystalline cordierite.SOLUTION: A honeycomb structure has a plurality of cell channels passing through the inside of the honeycomb structure and partitioned by a porous partition wall. The honeycomb structure contains 80.0 to 94.0 mass% of cordierite as a main crystal phase and ceria included in a sub-crystal phase. A porosity of the porous partition wall measured by a mercury intrusion method is 60% or more. In the porous partition wall, in a volume-based cumulative pore size distribution measured by the mercury intrusion method, a 10% accumulation pore diameter (D10), a 50% accumulation pore diameter (D50) and a 90% accumulation pore diameter (D90) from a small pore side satisfy a relation of (D90-D10) / D50≤1.2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a honeycomb structure and a manufacturing method thereof. [Background technology]

[0002] Exhaust gas emitted from internal combustion engines such as diesel engines contains a large amount of particulate matter (particulate matter) whose main component is carbon, which causes environmental pollution. For this reason, the exhaust systems of diesel engines and other engines are generally equipped with a filter (Diesel Particulate Filter: DPF) to capture particulate matter. In recent years, particulate matter emitted from gasoline engines has also become a problem, and gasoline engines are now also being equipped with a filter (Gasoline Particulate Filter: GPF).

[0003] Honeycomb structures are often used for such filters. Cordierite is often used as a material for forming honeycomb structures because of its high thermal shock resistance. A porous honeycomb structure mainly composed of cordierite can be manufactured by kneading a raw material composition obtained by appropriately adding a cordierite raw material, a dispersion medium, a pore-forming material, a binder, and various additives, making a clay, and extruding the clay through a predetermined die to produce a honeycomb-shaped molded body (honeycomb molded body), drying the honeycomb molded body, and then firing the honeycomb molded body.

[0004] Conventionally, honeycomb structures primarily composed of cordierite are required to have a high cordierite crystal content (phase) in order to ensure thermal shock resistance through low thermal expansion and to increase strength, and various raw material compositions and firing conditions have been investigated (Patent Documents 1 to 3).

[0005] In addition, porosity and pore size distribution are known to be parameters that affect the performance of honeycomb structures. Technologies have been developed to improve mechanical strength, thermal expansion coefficient, etc., and to reduce pressure loss when exhaust gas is passed through the honeycomb structures by controlling the porosity and pore size distribution (Patent Documents 4 to 8). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2008-207978 A [Patent Document 2] Japanese Patent Application Publication No. 6-263528 [Patent Document 3] Special Publication No. 2002-530262 [Patent Document 4] Special Publication No. 2009-542570 [Patent Document 5] Special Publication No. 2019-506289 [Patent Document 6] International Publication No. 2016 / 152236 [Patent Document 7] International Publication No. 2013 / 047908 [Patent Document 8] JP 2018-030105 A Summary of the Invention [Problem to be solved by the invention]

[0007] On the other hand, in a honeycomb structure having a high cordierite crystal amount (phase), there is still room for improvement in terms of achieving both high particulate collection efficiency and low pressure loss performance, and further performance improvement is required.

[0008] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a honeycomb structure that can achieve both high particulate collection efficiency and low pressure loss performance at a higher level while taking advantage of the excellent thermal shock resistance that is a characteristic of crystalline cordierite. In another embodiment, the present invention is to provide a method for manufacturing such a honeycomb structure. [Means for solving the problem]

[0009] The present inventors have found that cordierite crystals synthesized (sintered) from multiple raw materials, namely, magnesia source, silica source, and alumina source, tend to have a broad pore size distribution, which prevents the achievement of both high particulate collection efficiency and low pressure loss performance. The present invention has been completed based on this finding, and is exemplified below.

[0010] [Aspect 1] A honeycomb structure, The honeycomb structure has a plurality of cell channels passing through the inside thereof and separated by porous partition walls, Contains 80.0 to 94.0 mass% cordierite as a main crystalline phase and ceria contained in a secondary crystalline phase, The porous partition has a porosity of 60% or more as measured by mercury intrusion porosimetry; the porous partition wall has a cumulative pore size distribution on a volume basis measured by mercury intrusion porosimetry, in which the cumulative 10% pore size (D10), cumulative 50% pore size (D50), and cumulative 90% pore size (D90) from the small pore side satisfy the relationship of (D90-D10) / D50≦1.2; Honeycomb structure. [Aspect 2] 2. The honeycomb structure according to embodiment 1, wherein the porous partition walls have a cumulative 50% pore diameter (D50) of 10 to 20 μm. [Aspect 3] 3. The honeycomb structure according to embodiment 1 or 2, wherein the porous partition walls have a cumulative 10% pore diameter (D10) of 8 μm or more and a cumulative 90% pore diameter (D90) of 34 μm or less. [Aspect 4] 4. The honeycomb structure according to any one of aspects 1 to 3, wherein the secondary crystal phase further contains one or more compounds selected from mullite, spinel, sapphirine, and cristobalite. [Aspect 5] 5. The honeycomb structure according to embodiment 4, wherein the total content of ceria and one or more compounds selected from mullite, spinel, sapphirine, and cristobalite is 4.0 to 20.0% by mass. [Aspect 6] 6. The honeycomb structure according to any one of aspects 1 to 5, wherein the ceria content is 0.5 to 5.0 mass %. [Aspect 7] The linear expansion coefficient in the direction of the cell channel from 40°C to 800°C is 0.6×10 -6 / K~2.0×10 -6 7. The honeycomb structure according to any one of aspects 1 to 6, wherein the thickness of the honeycomb structure is 100 nm or more and the thickness of the honeycomb structure is 100 nm or more. [Aspect 8] A method for manufacturing a honeycomb structure, comprising: a step of kneading a raw material composition containing a cordierite raw material, ceria, a dispersion medium, a pore-forming material, and a binder to form a clay, and then extruding the clay to obtain a honeycomb formed body having a plurality of cell channels that pass through the inside of the honeycomb formed body and are partitioned by porous partition walls; A step of firing the honeycomb formed body; Including, In the firing step, the maximum temperature during firing is X (° C.), the holding time at the maximum temperature is Y (hr), and the content of ceria relative to 100 parts by mass of the cordierite-forming raw material in the honeycomb formed body is Z (parts by mass), 160≦(X-1345)×Y×(Z+0.5) 2 <=7680 A manufacturing method carried out so that the above formula holds true. Effect of the Invention

[0011] According to one embodiment of the present invention, it is possible to achieve both high particulate collection efficiency and low pressure loss performance at a higher level while taking advantage of the excellent thermal shock resistance that is a feature of crystalline cordierite. Therefore, the honeycomb structure can be suitably used as a filter that requires high performance. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a perspective view showing a typical wall-through type honeycomb structure. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a wall-through type honeycomb structure observed in a cross section parallel to the cell extension direction. [Diagram 3] FIG. 2 is a perspective view showing a typical wall-flow type columnar honeycomb structure. [Figure 4] FIG. 2 is a schematic cross-sectional view of a wall-flow type columnar honeycomb structure observed from a cross section parallel to the cell extension direction. [Diagram 5] FIG. 1 is an explanatory diagram illustrating an example of a method for forming plugging portions by a squeegee method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Next, an embodiment of the present invention will be described in detail with reference to the drawings. It should be understood that the present invention is not limited to the following embodiment, and that appropriate changes and improvements in the design may be made based on the ordinary knowledge of a person skilled in the art without departing from the spirit of the present invention.

[0014] (1. Honeycomb structure) A honeycomb structure according to one embodiment of the present invention has a plurality of cell channels that pass through the inside of the honeycomb structure and are partitioned by porous partition walls. In one embodiment, the honeycomb structure is provided as a wall-through type or wall-flow type columnar honeycomb structure. The use of the honeycomb structure is not particularly limited. For example, the honeycomb structure is used for various industrial applications such as heat sinks, filters (e.g., GPF, DPF), catalyst carriers, sliding parts, nozzles, heat exchangers, electrical insulating members, and semiconductor manufacturing equipment parts. In particular, the honeycomb structure can be suitably used as a filter that collects particulate matter contained in exhaust gas from an internal combustion engine, a boiler, etc., and a catalyst carrier for an exhaust gas purification catalyst. In particular, the honeycomb structure can be suitably used as an exhaust gas filter and / or a catalyst carrier for an automobile.

[0015] 1 and 2 are schematic perspective and cross-sectional views of a wall-through type honeycomb structure 100, respectively. The honeycomb structure 100 includes an outer peripheral side wall 102 and porous partition walls 112 disposed on the inner peripheral side of the outer peripheral side wall 102 and partitioning a plurality of cells 108 that form a fluid flow path (cell channel) from a first bottom surface 104 to a second bottom surface 106. In the honeycomb structure 100, both ends of each cell 108 are open, and exhaust gas that has flowed into one cell 108 from the first bottom surface 104 is purified while passing through the cell, and flows out from the second bottom surface 106. Here, the first bottom surface 104 is defined as the upstream side of the exhaust gas, and the second bottom surface 106 is defined as the downstream side of the exhaust gas, but the distinction between the first bottom surface and the second bottom surface is for convenience, and the second bottom surface 106 may be defined as the upstream side of the exhaust gas, and the first bottom surface 104 may be defined as the downstream side of the exhaust gas.

[0016] 3 and 4 are schematic perspective and cross-sectional views, respectively, of a wall-flow type honeycomb structure 200. This honeycomb structure 200 includes an outer peripheral side wall 202 and porous partition walls 212 disposed on the inner peripheral side of the outer peripheral side wall 202 and partitioning a plurality of cells 208a, 208b that form a fluid flow path (cell channel) from a first bottom surface 204 to a second bottom surface 206. In the honeycomb structure 200, the multiple cells 208a, 208b can be classified into multiple first cells 208a arranged inside the outer peripheral side wall 202, extending from the first bottom surface 204 to the second bottom surface 206, the first bottom surface 204 being open and having plugged portions 209 on the second bottom surface 206, and multiple second cells 208b arranged inside the outer peripheral side wall 202, extending from the first bottom surface 204 to the second bottom surface 206, having plugged portions 209 on the first bottom surface 204, and having an open second bottom surface 206. In this honeycomb structure 200, the first cells 208a and the second cells 208b are alternately arranged adjacent to each other with the porous partition wall 212 interposed therebetween.

[0017] When exhaust gas containing particulate matter such as soot is supplied to the first bottom surface 204 on the upstream side of the honeycomb structure 200, the exhaust gas is introduced into the first cells 208a and proceeds downstream inside the first cells 208a. Since the first cells 208a have plugged portions 209 on the second bottom surface 206 on the downstream side, the exhaust gas passes through the porous partition walls 212 that separate the first cells 208a and the second cells 208b and flows into the second cells 208b. Since the particulate matter cannot pass through the porous partition walls 212, it is collected and deposited inside the first cells 208a. After the particulate matter is removed, the clean exhaust gas that has flowed into the second cells 208b proceeds downstream inside the second cells 208b and flows out from the second bottom surface 206 on the downstream side. Here, the first bottom surface 204 is defined as the upstream side of the exhaust gas, and the second bottom surface 206 is defined as the downstream side of the exhaust gas, but the distinction between the first bottom surface and the second bottom surface is for convenience, and the second bottom surface 206 may be defined as the upstream side of the exhaust gas, and the first bottom surface 204 may be defined as the downstream side of the exhaust gas.

[0018] The shape of the bottom surface of the honeycomb structure is not limited, and may be, for example, a circular shape, an elliptical shape, a racetrack shape, an oval shape, or other round shape, a triangular shape, a rectangular shape, or other polygonal shape, or other irregular shape. The honeycomb structure shown in the figure has a circular bottom shape and is cylindrical as a whole.

[0019] The height of the honeycomb structure (the length from the first bottom surface to the second bottom surface) is not particularly limited, and may be appropriately set depending on the application and required performance. The height of the honeycomb structure may be, for example, 40 mm to 450 mm. There is also no particular limit to the relationship between the height of the honeycomb structure and the maximum diameter of each bottom surface (the maximum length of the diameters passing through the center of gravity of each bottom surface of the honeycomb structure). Therefore, the height of the honeycomb structure may be longer than the maximum diameter of each bottom surface, or the height of the honeycomb structure may be shorter than the maximum diameter of each bottom surface.

[0020] From the viewpoint of pressure loss, the lower limit of the porosity of the porous partition walls of the honeycomb structure measured by mercury porosimetry is preferably 60% or more, more preferably 62% or more. From the viewpoint of mechanical strength of the honeycomb structure, the upper limit of the porosity of the porous partition walls measured by mercury porosimetry is preferably 70% or less, more preferably 68% or less. Therefore, the porosity of the porous partition walls measured by mercury porosimetry is preferably, for example, 60 to 70%, more preferably 62 to 68%. In this specification, the "porosity" is measured by the mercury porosimetry specified in JIS R1655:2003. Moreover, the porosity is the average value of the porosity of each of the porous partition walls measured by mercury porosimetry without bias from six points of the porous honeycomb structure.

[0021] In addition, it is desirable for the porous partition wall to have a sharp pore size distribution in order to achieve both high particulate collection efficiency and low pressure drop performance at a higher level. Specifically, in the volume-based cumulative pore size distribution measured by mercury intrusion porosimetry, the porous partition wall preferably has a cumulative 10% pore size (D10), cumulative 50% pore size (D50), and cumulative 90% pore size (D90) from the small pore side satisfying the relationship (D90-D10) / D50≦1.2, more preferably satisfying the relationship (D90-D10) / D50≦1.1, and even more preferably satisfying the relationship (D90-D10) / D50≦1.0. Although the lower limit of (D90-D10) / D50 is 0, from the viewpoint of ease of production, it is normal for it to satisfy 0.5≦(D90-D10) / D50, and typically 0.8≦(D90-D10) / D50. Therefore, the porous partition wall can satisfy, for example, 0.5≦(D90-D10) / D50≦1.2, and preferably 0.8≦(D90-D10) / D50≦1.1.

[0022] Conventionally, when the porous partition wall has a high porosity as described above and contains a high ratio of crystalline cordierite, it has been difficult to obtain such a sharp pore size distribution. This is because it is difficult to control the pores formed during firing of cordierite crystals, so that the pore size distribution tends to be broad, and it is also difficult to control the pores originating from the gaps between the particles of the cordierite raw material. However, by setting the content of crystalline cordierite to a slightly lower level, adding ceria, and providing the manufacturing method with the ingenuity described below, it is possible to obtain such a sharp pore size distribution. This makes it possible to achieve both high particulate collection efficiency and low pressure loss performance at a higher level while taking advantage of the excellent thermal shock resistance that is a characteristic of crystalline cordierite.

[0023] In this specification, D10, D50 and D90 of the porous partition wall are measured by the mercury intrusion method defined in JIS R1655:2003 using a mercury porosimeter. Mercury intrusion is a method in which a sample is immersed in mercury under vacuum and a uniform pressure is applied, mercury is forced into the sample while gradually increasing the pressure, and the pore size distribution is calculated from the pressure and the volume of mercury forced into the pores. When the pressure is gradually increased, mercury is forced into the pores starting from the larger diameter pores, and the cumulative volume of mercury increases, and when all the pores are finally filled with mercury, the cumulative volume reaches an equilibrium amount. The cumulative volume at this time is the total pore volume (cm 3 / g). The pore diameter at the time when 10% of the total pore volume of mercury is injected from the small pore side is the cumulative 10% pore diameter (D10), the pore diameter at the time when 50% of the total pore volume of mercury is injected from the small pore side is the cumulative 50% pore diameter (D50), and the pore diameter at the time when 90% of the total pore volume of mercury is injected from the small pore side is the cumulative 90% pore diameter (D90).

[0024] Porous partition wall samples (0.3 g each) were collected from six locations of the honeycomb structure without bias, and the pore size distribution of each was measured to determine D10, D50 and D90, and the average value was taken as the measured value.

[0025] It is desirable to set the cumulative 50% pore size (D50) of the porous partition wall in an appropriate range depending on the application. For example, when the honeycomb structure is used for a filter, the D50 of the porous partition wall is preferably 20 μm or less, more preferably 18 μm or less. When the D50 of the porous partition wall is in the above range, the particulate matter collection efficiency is significantly improved. Furthermore, the D50 of the porous partition wall is preferably 10 μm or more, more preferably 12 μm or more. When the D50 of the porous partition wall is in the above range, an increase in pressure loss can be suppressed. Therefore, the D50 of the porous partition wall is, for example, preferably 10 to 20 μm, more preferably 12 to 18 μm.

[0026] Similarly, it is desirable to set the cumulative 10% pore size (D10) and cumulative 90% pore size (D90) of the porous partition wall to an appropriate range depending on the application. For example, when the honeycomb structure is used for a filter, it is preferable that D10 is 8 μm or more and D90 is 34 μm or less, more preferably D10 is 9 μm or more and D90 is 32 μm or less, and even more preferably D10 is 10 μm or more and D90 is 30 μm or less. Controlling D10 and D90 within such ranges is advantageous in achieving both high particulate collection efficiency and low pressure loss performance at a higher level.

[0027] From the viewpoint of making the pore size distribution sharp, the honeycomb structure preferably has a cordierite (2MgO·2Al2O3·5SiO2) content as the main crystalline phase of 80.0 mass% or more, and more preferably has a cordierite content as the main crystalline phase of 82.0 mass% or more. However, if the cordierite content as the main crystalline phase is too high, it becomes difficult to make the pore size distribution sharp. For this reason, the honeycomb structure preferably has a cordierite content as the main crystalline phase of 94.0 mass% or less, and more preferably has a cordierite content as the main crystalline phase of 90.0 mass% or less. Therefore, the honeycomb structure preferably has a cordierite content as the main crystalline phase of 80.0 to 94.0 mass%, and more preferably has a cordierite content as the main crystalline phase of 82.0 to 90.0 mass%.

[0028] From the viewpoint of sharpening the pore size distribution, the honeycomb structure (particularly the outer peripheral side wall and partition wall) preferably contains ceria in the sub-crystalline phase. Furthermore, from the viewpoint of sharpening the pore size distribution, the sub-crystalline phase preferably contains one or more compounds selected from mullite, spinel, sapphirine and cristobalite. From the viewpoint of sharpening the pore size distribution, the lower limit of the total content of ceria and one or more compounds selected from mullite, spinel, sapphirine and cristobalite in the honeycomb structure (particularly the outer peripheral side wall and partition wall) is preferably 4.0 mass% or more, more preferably 6.0 mass% or more, and even more preferably 8.0 mass% or more. The upper limit of the total content of ceria and one or more compounds selected from mullite, spinel, sapphirine and cristobalite in the honeycomb structure (particularly the outer peripheral side wall and partition wall) is preferably 20.0 mass% or less, more preferably 18.5 mass% or less, and even more preferably 17.5 mass% or less, from the viewpoint of collection performance. Therefore, in one embodiment, the total content of ceria and one or more compounds selected from mullite, spinel, sapphirine and cristobalite in the honeycomb structure (particularly the outer peripheral side wall and partition wall) is preferably 4.0 to 20.0 mass%, more preferably 6.0 to 18.5 mass%, and even more preferably 8.0 to 17.5 mass%.

[0029] The lower limit of the ceria content in the honeycomb structure (particularly the outer peripheral side wall and partition walls) is more preferably 0.5 mass% or more, and even more preferably 1.0 mass% or more, from the viewpoint of making the pore size distribution sharp. The upper limit of the ceria content in the honeycomb structure (particularly the outer peripheral side wall and partition walls) is preferably 5.0 mass% or less, and more preferably 4.0 mass% or less, from the viewpoint of collection performance. Therefore, in one embodiment, the ceria content in the honeycomb structure (particularly the outer peripheral side wall and partition walls) is preferably 0.5 to 5.0 mass%, and more preferably 1.0 to 4.0 mass%.

[0030] The content of the compounds such as ceria contained in the cordierite which is the main crystal phase in the honeycomb structure and in the secondary crystal phase is measured by the following method. A sample (3.0 g) of the porous partition wall is taken from two locations, the center in the radial direction at the center of the height direction of the honeycomb structure and near the outer periphery, and each is crushed to prepare a measurement sample. Each measurement sample is subjected to X-ray analysis measurement in the range of 2θ=8 to 100° by X-ray diffraction using Cu Kα radiation, and analyzed using the Rietveld analysis program RIETAN to determine the mass contents of cordierite, ceria, mullite, spinel, sapphirine, and cristobalite. The average value of the mass contents of each compound in the two measurement samples is defined as the mass content of each compound, and the sum of the average values ​​of the contents of each compound is defined as the total content.

[0031] It is preferable that the linear expansion coefficient of the honeycomb structure in the extension direction of the cell channels at 40° C. to 800° C. is low. For example, the honeycomb structure according to one embodiment of the present invention has a linear expansion coefficient of 0.6×10 -6 / K~2.0×10 -6 / K, typically 0.6 × 10 -6 / K~1.8×10 -6 / K. The linear expansion coefficient is measured in accordance with JIS R1618:2002.

[0032] Samples for measuring the linear expansion coefficient of a honeycomb structure are taken in the following manner. A rectangular columnar sample measuring 3 mm x 3 mm x 20 mm (length in the cell extension direction) is cut from the center of the honeycomb structure in the radial and height directions. The linear expansion coefficient of the sample is measured under the above-mentioned temperature change conditions, and this is taken as the measured value.

[0033] The average thickness of the partition walls in the honeycomb structure is preferably 152 μm or more from the viewpoint of ensuring strength, more preferably 178 μm or more, and even more preferably 203 μm or more. In addition, the average thickness of the partition walls is preferably 305 μm or less, more preferably 279 μm or less, and even more preferably 254 μm or less from the viewpoint of suppressing pressure loss. Therefore, the average thickness of the partition walls is, for example, preferably 152 to 305 μm, more preferably 178 to 279 μm, and even more preferably 203 to 254 μm. The thickness of the partition walls refers to the length of a line segment that crosses the partition walls when the line segment connects the centers of gravity of adjacent cells in a cross section perpendicular to the cell extension direction (height direction of the honeycomb structure). The average thickness of the partition walls refers to the average value of the thicknesses of all the partition walls.

[0034] In one embodiment, the plugging portions of both the first bottom face and the second bottom face have an average depth of 2 to 8 mm. When the average depth of the plugging portions is 2 mm or more, the strength of the plugging portions can be ensured. The average depth of the plugging portions is preferably 3 mm or more. Furthermore, when the average depth of the plugging portions is 8 mm or less, the area of ​​the partition walls that capture particulate matter in the cells can be prevented from becoming small. The average depth of the plugging portions is preferably 7 mm or less. The depth of the plugging portions in the cell extension direction is measured at any 20 points on each bottom face, and the average value is taken as the average depth of the plugging portions on each bottom face.

[0035] There is no particular restriction on the cell density (the number of cells per unit cross-sectional area) of the honeycomb structure, and it may be, for example, 6 to 2000 cells / square inch (0.9 to 311 cells / cm). 2 ), preferably 50 to 1000 cells / in2 (7.8 to 155 cells / cm2 2 ), more preferably 100 to 600 cells / in2 (15.5 to 92.0 cells / cm 2 Here, the cell density is calculated by dividing the total number of cells (including plugged cells) by one of the bottom areas excluding the outer peripheral side wall of the honeycomb structure.

[0036] When the honeycomb structure is used as a catalyst carrier, the surface of the partition wall can be coated with a catalyst according to the purpose. Examples of the catalyst include, but are not limited to, an oxidation catalyst (DOC) for increasing the exhaust gas temperature by oxidizing and burning hydrocarbons (HC) and carbon monoxide (CO), a PM combustion catalyst for assisting the combustion of PM such as soot, an SCR catalyst and an NSR catalyst for removing nitrogen oxides (NOx), and a three-way catalyst capable of simultaneously removing hydrocarbons (HC), carbon monoxide (CO), and nitrogen oxides (NOx). The catalyst can appropriately contain, for example, precious metals (Pt, Pd, Rh, etc.), alkali metals (Li, Na, K, Cs, etc.), alkaline earth metals (Mg, Ca, Ba, Sr, etc.), rare earths (Ce, Sm, Gd, Nd, Y, La, Pr, etc.), transition metals (Mn, Fe, Co, Ni, Cu, Zn, Sc, Ti, Zr, V, Cr, etc.), etc.

[0037] (2. Manufacturing method) A method for manufacturing a honeycomb structure according to an embodiment of the present invention will be described below by way of example. First, a raw material composition containing a cordierite raw material, a dispersion medium, a pore former, and a binder is kneaded to form a clay, and then the clay is extruded to obtain a honeycomb molded body having a plurality of cell channels that pass through the inside of the honeycomb molded body and are partitioned by porous partition walls. The honeycomb molded body has an outer peripheral side wall and is disposed on the inner peripheral side of the outer peripheral side wall, extends from the first bottom surface to the second bottom surface, and both the first bottom surface and the second bottom surface can have openings. The raw material composition may contain additives such as a dispersant or other ceramic raw materials as necessary. In the extrusion molding, a die having a desired overall shape, cell shape, partition wall thickness, cell density, etc. can be used.

[0038] The cordierite-forming raw material is a raw material that becomes cordierite by firing, and can be provided, for example, in the form of a powder. For example, talc, alumina, aluminum hydroxide, silica, etc. can be mixed in an appropriate ratio and used. The cordierite-forming raw material desirably has a chemical composition of 30 to 45 mass% alumina (Al2O3) (including the aluminum hydroxide converted to alumina), 11 to 17 mass% magnesia (MgO), and 42 to 57 mass% silica (SiO2).

[0039] In addition, from the viewpoint of making the pore size distribution sharp and from the viewpoint of promoting the formation of cordierite crystals at a relatively low temperature, it is preferable to add ceria as a sintering aid to the raw material composition. Therefore, the lower limit of the content of ceria in the raw material composition or the honeycomb formed body is preferably 0.5 parts by mass or more, more preferably 1.0 parts by mass or more, relative to 100 parts by mass of the cordierite-forming raw material. The upper limit of the content of ceria in the raw material composition or the honeycomb formed body is preferably 5.0 parts by mass or less, more preferably 4.0 parts by mass or less, relative to 100 parts by mass of the cordierite-forming raw material, from the viewpoint of collection performance, relative to 100 parts by mass of the cordierite-forming raw material. Therefore, in one embodiment, the content of ceria in the raw material composition or the honeycomb formed body is preferably 0.5 to 5.0 parts by mass, more preferably 1.0 to 4.0 parts by mass, relative to 100 parts by mass of the cordierite-forming raw material. The content of ceria in the honeycomb formed body relative to 100 parts by mass of the cordierite-forming raw material is equal to Z (parts by mass) described later.

[0040] From the viewpoint of enhancing the effect of sharpening the pore size distribution in the partition walls and the outer peripheral side walls of the honeycomb structure, the ceria added to the raw material composition has an upper limit of the median diameter (D50) in the cumulative particle size distribution on a volume basis determined by a laser diffraction / scattering method of 10 μm or less, more preferably 8 μm or less, and even more preferably 6 μm or less. From the viewpoint of the occurrence of internal defects due to aggregation, the ceria added to the raw material composition has a lower limit of the median diameter (D50) in the cumulative particle size distribution on a volume basis determined by a laser diffraction / scattering method of 0.1 μm or more, more preferably 0.3 μm or more, and even more preferably 0.5 μm or more. Therefore, for example, the median diameter (D50) of the ceria added to the raw material composition is preferably 0.1 to 10 μm, more preferably 0.3 to 8 μm, and even more preferably 0.5 to 6 μm.

[0041] The dispersion medium may be water or a mixed solvent of water and an organic solvent such as alcohol, with water being particularly preferred.

[0042] The content of the dispersion medium in the honeycomb molded body before the drying step is preferably 20 to 110 parts by mass, more preferably 25 to 100 parts by mass, and even more preferably 30 to 90 parts by mass, relative to 100 parts by mass of the cordierite-forming raw material. When the content of the dispersion medium in the honeycomb molded body is 20 parts by mass or more relative to 100 parts by mass of the cordierite-forming raw material, the advantage that the quality of the honeycomb structure is easily stabilized is easily obtained. When the content of the dispersion medium in the honeycomb molded body is 110 parts by mass or less relative to 100 parts by mass of the cordierite-forming raw material, the amount of shrinkage during drying is small, and deformation can be suppressed. In this specification, the content of the dispersion medium in the honeycomb molded body refers to a value measured by a drying loss method.

[0043] The pore-forming material is not particularly limited as long as it becomes pores after firing, and examples thereof include wheat flour, starch, foamed resin, water-absorbent resin, silica gel, carbon (e.g., graphite), ceramic balloons, polyethylene, polystyrene, polypropylene, nylon, polyester, acrylic polymer, and phenol. The pore-forming material may be used alone or in combination of two or more. The content of the pore-forming material is preferably 3 parts by mass or more, more preferably 6 parts by mass or more, and even more preferably 9 parts by mass or more, relative to 100 parts by mass of the cordierite raw material, from the viewpoint of increasing the porosity of the honeycomb structure after firing. The content of the pore-forming material is preferably 30 parts by mass or less, more preferably 27 parts by mass or less, and even more preferably 24 parts by mass or less, relative to 100 parts by mass of the cordierite raw material, from the viewpoint of ensuring the strength of the honeycomb structure after firing. The addition of ceria tends to reduce the porosity, so that the amount of pore-forming material required to achieve the same porosity tends to be greater than in the case where no ceria is added.

[0044] Examples of the binder include organic binders such as methyl cellulose, hydroxypropoxyl methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, carboxymethyl cellulose, and polyvinyl alcohol. The content of the binder is preferably 4 parts by mass or more, more preferably 5 parts by mass or more, and even more preferably 6 parts by mass or more, relative to 100 parts by mass of the cordierite raw material, from the viewpoint of increasing the strength of the honeycomb molded body before firing. The content of the binder is preferably 9 parts by mass or less, more preferably 8 parts by mass or less, and even more preferably 7 parts by mass or less, relative to 100 parts by mass of the cordierite raw material, from the viewpoint of suppressing the occurrence of breakage due to abnormal heat generation in the firing process. The binder may be used alone or in combination of two or more types.

[0045] The dispersant may be ethylene glycol, dextrin, fatty acid soap, polyether polyol, etc. The dispersant may be used alone or in combination of two or more. The content of the dispersant is preferably 0 to 5 parts by mass with respect to 100 parts by mass of the cordierite-forming raw material.

[0046] The honeycomb formed body can be dried by a conventionally known drying method such as hot air drying, microwave drying, dielectric drying, reduced pressure drying, vacuum drying, freeze drying, etc. Among these, a drying method that combines hot air drying with microwave drying or dielectric drying is preferred because it can quickly and uniformly dry the entire honeycomb formed body.

[0047] When manufacturing a honeycomb structure having plugging portions, the openings of predetermined cells of a honeycomb formed body or a dried body obtained by drying the formed body may be plugged with a plugging material. Each plugging portion can be formed by filling the openings of the first and second cells where the plugging portions are to be formed with a plugging portion forming slurry, and then drying and firing the filled slurry. The plugging portion forming slurry may be prepared according to a known composition, and may contain, for example, a cordierite raw material, a dispersion medium, a pore former, and a binder. The plugging portion forming slurry may contain ceria.

[0048] For example, the plugging portion forming slurry contains 30 to 60 parts by mass of a dispersion medium, 5 to 20 parts by mass of a pore-forming material, and 0.2 to 2.0 parts by mass of a binder with respect to 100 parts by mass of a cordierite-forming raw material. In a preferred embodiment, the plugging portion forming slurry contains 35 to 50 parts by mass of a dispersion medium, 8 to 16 parts by mass of a pore-forming material, and 0.2 to 1.5 parts by mass of a binder with respect to 100 parts by mass of a cordierite-forming raw material.

[0049] The dispersion medium may be water or a mixed solvent of water and an organic solvent such as alcohol, with water being particularly preferred.

[0050] The pore-forming material is not particularly limited as long as it becomes pores after firing, and examples thereof include wheat flour, starch, foamed resin, water-absorbent resin, silica gel, carbon (e.g., graphite), ceramic balloons, polyethylene, polystyrene, polypropylene, nylon, polyester, acrylic resin, phenol, etc. The pore-forming material may be used alone or in combination of two or more kinds.

[0051] Examples of the binder include organic binders such as methyl cellulose, hydroxypropoxyl methyl cellulose, hydroxypropyl methyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, carboxymethyl cellulose, polyvinyl alcohol, etc. The binder may be used alone or in combination of two or more kinds.

[0052] The plugging portion forming slurry may contain a dispersant as appropriate. For example, the dispersant may be contained in an amount of 0 to 2.0 parts by mass relative to 100 parts by mass of the cordierite forming raw material. Examples of the dispersant include ethylene glycol, dextrin, fatty acid soap, and polyalcohol. The dispersant may be used alone or in combination of two or more kinds.

[0053] The openings of the cells can be filled with the plugging portion forming slurry, for example, by the following "squeegee method." As shown in Fig. 5, a film 121 is attached to the upper bottom surface (here, the second bottom surface 106 in the figure) of the dried honeycomb formed body 500 fixed using a chuck 120, and a laser is irradiated to the film 121 at positions corresponding to the arrangement conditions of the plugging portions (for example, "checkered pattern"), and a plurality of holes 126 are formed in the film 121.

[0054] Thereafter, the plugging portion forming slurry 124 is placed on the film 121, and the squeegee 122 is moved along the film 121 in the direction of the arrow in Fig. 5. As a result, a certain amount of the plugging portion forming slurry 124 is filled into the cells 125 that are opened at positions corresponding to the holes 126 of the film 121.

[0055] The depth of the plugging portion can be changed by the number of times the squeegee 122 is moved, the contact angle between the squeegee 122 and the film 121, the pressing pressure of the squeegee 122 against the film 121, and the viscosity of the plugging portion forming slurry 124, etc.

[0056] After filling the plugging portion forming slurry 124, the film 121 is peeled off, and the entire honeycomb formed body 500 is dried. As a result, the plugging portion forming slurry 124 filled in the cells 125 is dried, and plugging portions before firing are formed. The drying can be performed, for example, under conditions of a drying temperature of 100 to 230°C for about 60 to 100 seconds. After drying, the plugging portions protrude from the bottom surface of the honeycomb formed body by the thickness of the film, and can be scraped off as necessary.

[0057] The material of the film is not particularly limited, but is preferably polypropylene (PP), polyethylene terephthalate (PET), polyimide, or Teflon (registered trademark) because it is easy to heat process to form holes. The film also preferably has an adhesive layer, and the material of the adhesive layer is preferably an acrylic resin, a rubber-based material (e.g., a rubber whose main component is natural rubber or synthetic rubber), or a silicon-based resin. For example, an adhesive film having a thickness of 20 to 50 μm can be suitably used as the film.

[0058] In addition to the above-mentioned "squeegee method," another method for filling the openings of the cells with the plugging portion forming slurry is the "press-in method." The "press-in method" is a method in which the bottom surface of a honeycomb formed body with a film attached and holes drilled therein is immersed in a liquid tank containing the plugging portion forming slurry, and the cells are filled with the plugging portion forming slurry. In this case, the depth of the plugging portions can be changed by the depth to which the honeycomb formed body is immersed in the plugging portion forming slurry.

[0059] The honeycomb formed body filled with the plugging portion forming slurry as required is then subjected to a degreasing process and a firing process, thereby manufacturing a honeycomb structure. The combustion temperature of the binder is about 200°C, and the combustion temperature of the pore-forming material is about 300 to 1000°C. Therefore, the degreasing process may be carried out by heating the honeycomb formed body to a temperature range of about 200 to 1000°C. The heating time is not particularly limited, but is usually about 10 to 100 hours. The honeycomb formed body after the degreasing process is called a calcined body.

[0060] In the firing process, when the maximum temperature during firing is X (°C), the holding time at the maximum temperature is Y (hr), and the ceria content per 100 parts by mass of the cordierite-forming raw material in the honeycomb molded body is Z (parts by mass), in order to ensure the necessary amount of cordierite crystals while sharpening the pore size distribution, it is preferable to perform the firing process so that (Equation 1) is satisfied, more preferably so that (Equation 2) is satisfied, and even more preferably so that (Equation 3) is satisfied. 160≦(X-1345)×Y×(Z+0.5) 2 ≦7680 (Formula 1) 160≦(X-1345)×Y×(Z+0.5) 2 ≦4840 (Formula 2) 160≦(X-1345)×Y×(Z+0.5) 2 ≦3720 (Formula 3) The firing step is preferably carried out on the calcined body. Mullite, spinel, sapphirine and cristobalite do not need to be added to the raw material composition, and appropriate amounts are produced as by-products during firing under the above conditions, forming a secondary crystal phase.

[0061] From the viewpoint of achieving a sharp pore size distribution, X (°C) is preferably 1430 or less, more preferably 1400 or less, and even more preferably 1380 or less. From the viewpoint of promoting the formation of cordierite crystals, X (°C) is preferably 1345 or more, more preferably 1350 or more, and even more preferably 1355 or more. Therefore, X (°C) is, for example, preferably 1345 to 1430, more preferably 1350 to 1400, and even more preferably 1355 to 1380.

[0062] From the viewpoint of ease of production, Y(hr) is preferably 24 or less, and more preferably 16 or less. From the viewpoint of promoting the formation of cordierite crystals, Y(hr) is preferably 7 or more, and more preferably 12 or more. Therefore, Y(hr) is preferably, for example, 7 to 24, and more preferably 12 to 16.

[0063] The preferred conditions for Z (parts by mass) are as described above. EXAMPLES

[0064] The following examples are provided to better understand the present invention and its advantages, but the present invention is not limited to these examples.

[0065] <Production of honeycomb structure (Comparative Examples 1 to 5, Examples 1 to 9)> (1) Preparation of columnar honeycomb body A raw material composition obtained by adding the cordierite raw material, dispersion medium, pore former, binder, dispersant, and sintering aid in the mass ratios shown in Table 1 was kneaded to prepare a clay. Talc, alumina, aluminum hydroxide, and silica were used as the cordierite raw materials. Water was used as the dispersion medium. An acrylic polymer was used as the pore former. Methyl cellulose was used as the binder, and ethylene glycol was used as the dispersant. Ceria (median diameter in the cumulative particle size distribution on a volume basis determined by a laser diffraction / scattering method = 1.0 μm) was used as the sintering aid.

[0066] The clay was put into an extrusion molding machine and extruded through a die of a predetermined shape to obtain a cylindrical honeycomb molded body. The obtained cylindrical honeycomb molded body was subjected to dielectric drying and hot air drying, and then further hot air drying, after which both bottom surfaces were cut to a predetermined dimension.

[0067] (2) Formation of plugging parts 40 parts by mass of the dispersion medium, 10 parts by mass of the pore former, 2 parts by mass of the binder, and 1 part by mass of the dispersant were added to 100 parts by mass of the cordierite raw material, and kneaded to prepare a slurry for forming plugged portions. Talc, alumina, aluminum hydroxide, and silica were used as the cordierite raw material. Water was used as the dispersion medium, foamed resin was used as the pore former, methyl cellulose was used as the binder, and ethylene glycol was used as the dispersant. Using the "squeegee method" described above, this slurry for forming plugged portions was filled on both bottom surfaces so that the first cells and the second cells were alternately arranged adjacent to each other. After that, it was dried under the conditions of 180°C x 200 seconds in an air atmosphere.

[0068] (3) Firing Next, the honeycomb structure was degreased by heating at about 200°C in an air atmosphere, and then fired in an air atmosphere at the maximum temperature and for the holding time at the maximum temperature shown in Table 1, to obtain a columnar honeycomb structure having plugged portions. When the maximum temperature during firing is X (°C), the holding time at the maximum temperature is Y (hr), and the content of ceria relative to 100 parts by mass of the cordierite-forming raw material in the honeycomb formed body is Z (parts by mass), the formula (X-1345)×Y×(Z+0.5) 2 The values ​​are shown in Table 1. The pillar-shaped honeycomb structures were manufactured in the number required for the following tests.

[0069] (4) Specifications of honeycomb structure The specifications of the obtained honeycomb structure are as follows. Overall shape: Cylinder with diameter 132mm x height 152mm Cell shape in cross section perpendicular to the flow direction: Square Cell density (number of cells per unit cross-sectional area): 300 cells / sq. in. (47 cells / cm 2 ) Average bulkhead thickness: 8.5 mil (216 μm) (nominal value based on cap specifications) Average plugging depth: 5mm

[0070] <Characteristics evaluation> Various characteristics of each honeycomb structure obtained above were evaluated.

[0071] (1. Porosity) The porosity (%) of the honeycomb structure was determined by the above-mentioned mercury intrusion method. The results are shown in Table 1.

[0072] (2. Pore size distribution of porous partition walls) The volume-based cumulative pore size distribution of the porous partition walls of the honeycomb structure was measured by the above-mentioned mercury intrusion method, and the cumulative 10% pore size (D10), cumulative 50% pore size (D50), cumulative 90% pore size (D90), and (D90-D10) / D50 from the small pore side were obtained. The results are shown in Table 1.

[0073] (3. Coefficient of Linear Expansion: CTE) Samples were taken from the center of the honeycomb structure in the radial and height directions by the above-mentioned method, and the linear expansion coefficient of the honeycomb structure in the extending direction of the cell channel at 40° C. to 800° C. was measured in accordance with JIS R1618: 2002. The results are shown in Table 1.

[0074] (4. Composition analysis) The honeycomb structure was subjected to composition analysis by the X-ray diffraction method described above using an X'pert PRO device manufactured by PANalytical, and the mass contents of cordierite, mullite, spinel, sapphirine, cristobalite, and ceria were measured. The results are shown in Table 1.

[0075] (5. Evaluation of filter performance) (5-1) Collection performance The honeycomb structure was connected to the outlet side of the engine exhaust manifold of a 1.2L direct injection gasoline engine vehicle, and the number of soot particles contained in the gas discharged from the outlet of the exhaust gas purification device was measured by the PN measurement method. Regarding the driving mode, a driving mode (RTS95) simulating the worst case of RDE driving was performed. The cumulative number of soot particles discharged after the driving mode was taken as the number of soot particles in the honeycomb structure to be evaluated, and the collection efficiency (%) was calculated from the number of soot particles. In the "collection performance" column of Table 1, the value of the collection efficiency of the honeycomb structure of Comparative Example 1 was taken as 100%, and the honeycomb filters of each Example and Comparative Example were evaluated based on the following evaluation criteria. The results are shown in Table 1. Evaluation: ◎: When the collection efficiency ratio (%) is over 110% Evaluation: "Good": When the collection efficiency ratio (%) is greater than 105% and less than 110% Evaluation: "△": When the collection efficiency ratio (%) is greater than 100% and less than 105% Evaluation: "X": Collection efficiency ratio (%) is 100% or less

[0076] (5-2) Pressure loss Exhaust gas from a 1.2L direct injection gasoline engine was heated to 700℃ and then cooled to 600m 3 / h, and the pressure was measured on the inlet end face side and the outlet end face side of the honeycomb structure. The pressure difference between the inlet end face side and the outlet end face side was calculated to determine the pressure loss (kPa) of the honeycomb structure. The "Pressure Loss" column in Table 1 shows the pressure loss values ​​(%) of the honeycomb structures of each Example and Comparative Example, when the pressure loss value of the honeycomb structure of Comparative Example 1 is set to 100%. In the pressure loss evaluation, the honeycomb filters of each Example were evaluated based on the following evaluation criteria. The results are shown in Table 1. Evaluation: ◎: Pressure loss ratio (%) is 90% or less Evaluation: "Good": When the pressure loss ratio (%) is greater than 90% and less than 95% Evaluation: "△": When the pressure loss ratio (%) is greater than 95% and less than 100% Evaluation: "X": When the pressure loss ratio (%) exceeds 100%

[0077] (5-3) Thermal shock resistance The honeycomb structure was placed in an electric furnace preheated to room temperature + 550°C, and heated for a sufficient time (30 minutes) for the entire honeycomb structure to reach the same temperature as the heating temperature of the electric furnace, and then air-cooled to room temperature at a cooling rate of 50°C / min. The honeycomb structure was inspected for cracks on the side, end, or inside due to the thermal shock during this cooling. If no cracks were generated when cooled to room temperature, it was considered that the heating temperature was cleared. The presence or absence of cracks was inspected visually, by tapping, etc. For the honeycomb structures that cleared the test, the heating temperature of the electric furnace was increased in 50°C steps, and the above test was repeated until cracks were generated. In the evaluation of thermal shock resistance, the honeycomb filters of each embodiment were evaluated based on the following evaluation criteria. The results are shown in Table 1. Evaluation: "X": When cracks occur at room temperature + 550℃ Evaluation: "△": If cleared up to room temperature + 550℃ Evaluation: "Good": If cleared up to room temperature + 600℃ Evaluation: "◎": If it clears up to room temperature + 650℃

[0078] [Table 1]

[0079] (6. Discussion) From the results in Table 1, it is seen that the honeycomb structures according to the examples of the present invention have achieved high levels of thermal shock resistance, high particulate collection efficiency, and low pressure loss performance. Comparative Examples 1 to 4 were inappropriate in at least one of the cordierite content, porosity, the presence or absence of ceria, and (D90-D10) / D50, and therefore were rated as x in the collection performance or pressure loss. [Explanation of symbols]

[0080] 100: Honeycomb structure 102: Outer wall 104: First bottom surface 106: Second bottom surface 108: Cell 112: Porous partition wall 120: Zipper 121: Film 122: Squeegee 124: Plugging slurry 125: Cell 126: Hole 200: Honeycomb structure 202: Outer wall 204: First bottom surface 206: Second bottom surface 208a: First cell 208b: Second cell 209: Plugging part 212: Porous partition wall 500: Honeycomb molding

Claims

1. A honeycomb structure, The honeycomb structure has a plurality of cell channels passing through the inside thereof and separated by porous partition walls, Contains 80.0 to 94.0 mass% cordierite as a main crystalline phase and ceria contained in a secondary crystalline phase; The porous partition wall has a porosity of 60% or more as measured by mercury intrusion porosimetry; the porous partition wall has a cumulative pore size distribution on a volume basis measured by mercury intrusion porosimetry, in which a cumulative 10% pore size (D10), a cumulative 50% pore size (D50), and a cumulative 90% pore size (D90) from the small pore side satisfy a relationship of (D90-D10) / D50≦1.2; Honeycomb structure.

2. 2. The honeycomb structure according to claim 1, wherein the porous partition walls have a cumulative 50% pore diameter (D50) of 10 to 20 μm.

3. 2. The honeycomb structure according to claim 1, wherein the porous partition walls have a cumulative 10% pore diameter (D10) of 8 μm or more and a cumulative 90% pore diameter (D90) of 34 μm or less.

4. 3. The honeycomb structure according to claim 1, wherein the secondary crystal phase further contains one or more compounds selected from the group consisting of mullite, spinel, sapphirine and cristobalite.

5. 5. The honeycomb structure according to claim 4, wherein the total content of ceria and one or more compounds selected from mullite, spinel, sapphirine and cristobalite is 4.0 to 20.0 mass %.

6. 3. The honeycomb structure according to claim 1, wherein the ceria content is 0.5 to 5.0 mass %.

7. 6. The honeycomb structure according to claim 5, wherein the ceria content is 0.5 to 5.0 mass %.

8. The linear expansion coefficient in the direction of the cell channel from 40°C to 800°C is 0.6 x 10 -6 / K ~ 2.0 x 10 -6 3. The honeycomb structure according to claim 1, wherein the ratio of the thickness of the honeycomb structure to the thickness of the honeycomb structure is 1 / K.

9. A method for manufacturing a honeycomb structure, comprising: a step of kneading a raw material composition containing a cordierite raw material, ceria, a dispersion medium, a pore-forming material, and a binder to form a clay, and then extruding the clay to obtain a honeycomb formed body having a plurality of cell channels that pass through the inside of the honeycomb formed body and are partitioned by porous partition walls; A step of firing the honeycomb formed body; Including, In the firing step, the maximum temperature during firing is X (° C.), the holding time at the maximum temperature is Y (hr), and the content of ceria relative to 100 parts by mass of the cordierite-forming raw material in the honeycomb formed body is Z (parts by mass), 160≦(X-1345)×Y×(Z+0.5) 2 ≦7680 A manufacturing method carried out so that the above formula is satisfied.